Designing Application Decision Support System For Science Olympics Participants Election In SMPN Sijunjung Using Analytical Hierarchy Process Methods - Rianti, Eva; Pratama, Robby Noval (Jurnal Sains dan Informatika, 2016)
One of the government programs to improve the quality of human resources through the Ministry of Education is to organize the National Science Olympiade (OSN). Therefore, every school are required to send their students to participate in the Olympics event. Before sending students will participate in the National Science Olympiad, the school has some selection process to choose the students who will participate in an Olympic event. From previous experience, the selection of participants randomly based on the best value in the capture of the semester students. It takes a long time in making decisions. In addition, frequent errors in determining the students who are competent in accordance with a field of science that they have mastered. Based on the problem above, designed decision support system that can help in decision-making. This system can provide convenience to the school at the time of selecting the students who will follow the Olympics, namely using Analytical Hierarchy Process (AHP).